Efficacy and Mediators of a Web-Based Media Literacy Intervention for Indoor Tanning Prevention. Issue 2 (1st February 2020) - Cho, Hyunyi; Song, Chi (Chuck); Adams, Dinah
Abstract : Extant media literacy interventions have been delivered in person, limiting their potential for large scale reach, implementation, and dissemination. Although emerging evidence suggests the interventions can impact behavior, the theoretical mediators that can explain the efficacy remain unknown. This study investigated the efficacy and mediators of a web-based media literacy intervention for reducing indoor tanning behavior among young women. Participants were randomly assigned to one of three conditions: a media literacy intervention with counter argument production, a media literacy intervention with counter story production, or an assessment-only control condition. The outcomes of indoor tanning behavior and intention were evaluated with 3- and 6-month follow-ups. Results indicated significant effects of the web-based intervention on reducing indoor tanning behavior at the follow-ups. Changes in perceived media realism completely mediated the intervention effects on behavior. Perceived media realism, positive and negative outcome expectancies, and collective efficacy partially mediated intervention effects on intention. This study demonstrates the efficacy of a web-based media literacy intervention and the theoretical mechanisms underlying the efficacy. It indicates that by altering perceived media realism, outcome expectancies, and collective efficacy, web-based media literacy interventions could generate behavioral effects.